Causales de suspensión del contrato individual de trabajo frente al derecho de estabilidad laboral - Cuenca Minga, Ángel Gonzalo (2022)
This legal investigation entitled "GROUNDS FOR SUSPENSION OF THE INDIVIDUAL EMPLOYMENT CONTRACT AGAINST THE RIGHT TO LABOR STABILITY" refers to the need to regulate and implement legal mechanisms in labor matters to better guarantee the rights of Ecuadorian workers since the current The Labor Code is a norm that has been in force for many years and does not have clear norms and efficient mechanisms that are in accordance with the current social needs of the country. The health emergency caused by the coronavirus (COVID-19) has generated several impacts for humanity worldwide and Ecuador has not been the exception since in the workplace it has caused many employers to be forced to suspend or permanently close their activities. thereby generating countless arbitrary and unfair dismissals, thus producing the violation of the right to work and the right to job stability, rights that allow workers and their families to obtain the necessary means to survive. Likewise, the health emergency has caused the Ecuadorian State to implement labor regulations that are not beneficial for the worker, since they allow the employer some arbitrariness in decision-making, leaving the worker at a clear disadvantage, who is the weakest part of the relationship. worked. Although it is true that the Constitution of the Republic of Ecuador in its article 33 consecrates work as a right and social duty and in its article 325 clearly states that the State must guarantee all people a decent job, it is worth asking if this right in the practice is effectively guaranteed since the unemployment rates in the country are very high. It is for this reason that today it is necessary to strengthen and implement labor mechanisms that ensure the full exercise of the rights of all workers with which it is possible to combat the problems that may arise in the future, either due to a situation such as the ones that we are going through or due to other unforeseen circumstances, always considering the protection of the worker. However, the legal figure of suspension of the individual employment contract is of vital importance within labor law since the purpose of this legal figure is to avoid the termination of the employment relationship between the employer and the worker and therefore seeks to keep the bond alive. labor, that is, it is a manifestation of the right to job stability; so much so that, once the causes that gave rise to the suspension have been overcome, the employment relationship is resumed under the existing conditions. Among the causes that are intended to be incorporated and originate the suspension of the individual work contract we have: Due to force majeure or fortuitous event that prevents its execution, due to the death or disqualification of the employer, when he is a natural person, due to suspension of activities or closure of the company for technical, economic reasons or due to lack of raw material, due to a temporary license or permit granted by the employer to the worker, due to the deprivation of liberty of the worker, as long as there is no conviction, decision of the worker who is forced 5 to abandon his job as a result of being a victim of gender-based violence by the employer or vice versa, incapacity of workers due to occupational or occupational disease or work accident, due to paternity, birth, adoption, risk during pregnancy or risk during lactation of the worker , exercise of public office representative of the worker, etc. The current Labor Code does not regulate in a clear and precise way the legal concept of the suspension of the individual work contract and its causes, since said labor figure is not regulated, it has caused many employers, taking advantage of the health emergency, to carry out countless dismissals of workers. workers producing high rates of unemployment and therefore the violation of fundamental rights of workers for this reason it is vitally important to incorporate the grounds for suspension of the employment contract in our labor legal system since it would avoid leaving many workers unemployed and prevent Many employer companies go bankrupt due to unforeseen situations that may arise during the course of the contract. Finally, within the present investigation, materials, methods and techniques that include surveys and interviews were applied, among them it was established whether or not there was a need to propose a project of legal reforms to the Labor Code aimed at strengthening the rights of workers and incorporate the grounds for suspension of the individual employment contract as rules that guarantee the effective enjoyment of rights, specifically the right to work and the right to job stability. Finally, this research was carried out under the institutional methodological guidelines and pertinent to the problem that was identified, planned and executed.